Assessment of a genetic contribution to osteoarthritis of the hip: sibling study. Issue 7270 (11th November 2000) - Lanyon, Peter; Muir, Kenneth; Doherty, Sally; Doherty, Michael
Abstract: Objectives: To study the influence of genetics on the development of hip osteoarthritis as determined by structural change on plain radiographs. Design: Sibling study. Setting: Nottinghamshire, England. Participants: 392 index participants with hip osteoarthritis of sufficient severity to warrant total hip replacement, 604 siblings of the index participants, and 1718 participants who had undergone intravenous urography. Main outcome measure: Odds ratios for hip osteoarthritis in siblings. Results: The age adjusted odds ratios in siblings were 4.9 (95% confidence interval, 3.9 to 6.4) for probable hip osteoarthritis and 6.4 (4.5 to 9.1) for definite hip osteoarthritis. These values were not significantly altered by adjusting for other risk factors. Conclusion: Siblings have a high risk of hip osteoarthritis as shown by structural changes on plain radiographs. One explanation is that hip osteoarthritis is under strong genetic influence.